ANALISIS PENGARUH PENAMBAHAN TEPUNG ISI RUMEN SAPI DALAM RANSUM AYAM LAYER TERHADAP KUALITAS KERABANG TELUR - Andi Suarda (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2011)
. This Research aim to to get picture until how far influence of addition of flour fill ox rumen in chicken ration of layers to eggs quality. Material which used in this research is layer chickens of production phase amount to 48 tail, old age nine months, and strain super Harco C.P 306 coming from Glorious PT.Charoen Pokhpan Farm, Jakarta. The Chicken looked after in 24 fairish each cage 1×0,5×1m made of cleft of bamboo which is width 2 cm lapped over with distance 1,5 - 2 cm. used to cage pallet consist of paddy chaff and of Slat. Location of chicken in cage done at random, where each;every cage filled two heads chicken equiped each one place eat and drink. Place eat and drink to be put down in such a manner in cage, so that each;every chicken get is same opportunity to eat and drink. giving of food done by ad-libitum. Fill ox rumen obtained from animal slaughter in Makassar. Device Attempt the used is Complete Random Device of Factorial Pattern 4 × 2 with thrice restating. First Factor is type of ransom, what consist of R-1 that is ransum without using flour fill ox rumen, R-2 is pregnant ransum 2,5 % flour fill ox rumen, R-3 is pregnant ransum 5 % flour fill ox rumen, R-4 is pregnant ransom 7,5 % flour fill ox rumen.. While both factor is cage pallet type which consist of Chaff Paddy and of Slat.Variables which measured in this research is thick of eggs skin. Key words; egg–skin, ox rumen, ration..